Bivalent polyether ionophores: Synthesis and biological evaluation of C2-symmetric salinomycin dimers. Issue 24 (14th June 2017) - Antoszczak, Michał; Maj, Ewa; Borgström, Björn; Oredsson, Stina; Huczyński, Adam; Wietrzyk, Joanna; Strand, Daniel
Graphical abstract: Highlights: Two novel classes of C2 -symmetric salinomycin dimers were designed and synthesized. TheC20- dimer was synthesized using a selective bi-directional acylation reaction. The C1 1, 3-diyne dimers were synthesized using a Cu(I)-catalysed Glaser-type coupling. The C20 dimer exhibited activity against cancer cell lines at micromolar concentrations. The C20 dimer showed low toxicity against normal (non-cancer) cells. Abstract: Efficient methods for the synthesis of C2 -symmetric dimers of salinomycin joined at either the C1 or C20 positions are reported. Similarly to the native structure, the C20- O -terephthalate dimer displayed activity in the low μM range against a series of cancer cell lines, while dimers joined at the C1 position were essentially inactive.